Deepening the analysis of literary texts among university students using close reading and writing: A pilot study - Duarte, António (2020)
This essay offers an analysis of the findings derived from a pedagogical case study performed with university students. This study set out to evaluate the effects training in close reading and close writing, applied to literary fictional texts, had on the structural complexity of narrative analysis (SCNA) of participating students. Participants’ perceptions of the impact of this training on their reading and writing skills was also monitored. SCNA was measured using Biggs and Collis (1982) SOLO taxonomy and qualitative thematic analysis was employed to analyse a focus-group interview on the impact of the training. The sample was randomly divided into two equivalent groups, one experimental (EG), the other control (CG). Both groups did three evaluations to access SCNA at the same time intervals: pre-training, post-training and follow-up timings of the EG. The CG only received training after they completing all three evaluations. While pre-training results demonstrated similarity across groups at the outset of trial after training, the EG’s SCNA increased significantly from pre-test to post-test and became significantly higher than the CG’s, which did not differ significantly. The EG’s gains were maintained in follow-up. Finally, the interview demonstrated that participants in the EG perceived that the training improved their reading and writing skills.